Health personnel in the pandemic: working at a permanent risk threshold - Hudson, Juan Pablo (2021)
This article presents some of the most relevant findings of a qualitative research that included fifteen interviews with health workers (doctors, kinesiologists and nurses) who work in areas of care for patients with Covid-19 in public hospitals and private clinics in seven provinces of Argentina.The objective was to highlight the transformations in their daily routines, with a particular emphasis on the consequences that the emergence of new occupational risks brought. The main hypothesis states that since the emergence of the pandemic, health personnel, especially those working in the Intensive Care Units, began to work at a risk threshold. That is, in a daily relationship with an imminent or effective health catastrophe, which caused physical and psychosocial symptoms and sufferings even in the case of those that had a vast experience. If anything was intensely modified, it was the historical relationship with patients and their families, as well as with their co-workers, as a consequence of the unprecedented contagiousness of this virus and the permanent inclusion of new care protocols.